PENERAPAN LATIHAN RANGE OF MOTION (ROM) CYLINDRICAL GRIP TERHADAP KEKUATAN OTOT EKSTREMITAS ATAS PADA PENDERITA STROKE NON HEMORAGIK DENGAN MASALAH KEPERAWATAN GANGGUAN MOBILITAS FISIK - Purwanti, Lina Ema; Novianti, Andhika Alfa (Universitas Muhammadiyah Ponorogo, 2024)
Impaired physical mobility is a result of blocked blood vessels due to stroke. Functions lost due to motor disorders in stroke patients result in extremity dysfunction, there by reducing muscle strength. A form of management to restore muscle strength in non-hemorrhagic stroke patients is Range of Motion (ROM) Cyindrical Grip which is useful for improving the ability to move joints normally to increase muscle mass. Nursing care for Mrs. R with nursing problems with physical mobility disorders is carried out in the KH. Ahmad Dahlan Room RSU Muhammadiyah of Ponorogo for 6 days from 28 July to 02 August 2023. The method used is a case study with a nursing process approach. The results of the assessment showed that the client experienced weakness in the left limb and a history of hypertension. The nursing action taken to overcome the problem is by implementing the ROM Cylindrical Grip exercise. It can be concluded that the ROM Cylindrical Grip can increase the muscle strength of the upper extremities in non-hemorrhagic stroke sufferers. After doing 2 x 10 minutes of exercise for 5 days, the muscle strength of the upper extremities in non-hemorrhagic stroke sufferers increased from 0 to 1. The results of this study, if the ROM Cylindrical Grip was carried out periodically and continuously, resulted in gripping muscle strength in non-hemorrhagic stroke sufferers increase.Keyword: Impaired Physical Mobility, Muscle Strength, ROM Cylindrical Grip, Non Hemorrhagic Stroke